Urinary tract infections in the menopausal period: optimal management - Milart, Paweł; Woźniakowska, Ewa; Woźniak, Sławomir; Palacz, Tomasz; Czuczwar, Piotr; Wrona, Wojciech; Szkodziak, Piotr; Paszkowski, Maciej; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
Urinary tract infections (UTI) are among the most common infectious diseases in women. They are observed particularly frequently in two groups of patients at different life stages, i.e., in young and sexually active women, and in postmenopausal women. This paper summarizes the current state of knowledge in the field of treatment of postmenopausal UTI. Uncomplicated cystitis is a complex illness of multifactorial etiology, and various risk factors have to be considered during woman’s lifespan. In the postmenopause, well-known UTI risk factors are post-voiding residual urine, reduced urinary flow, urinary incontinence and pelvic floor dysfunction. Behavioral risk factors should also be considered. The drop of estrogens concentration typical of menopause may suggest the auxiliary management option in cases of UTI in this age group. On the basis of recent literature review, the following conclusions seem to be justified: • The great majority of uncomplicated urinary tract infections in women are caused by Escherichia coli, independent of the patient’s hormonal status. • Fosfomycin, nitrofurantoin, ciprofloxacin and amox-clavulanate are most commonly recommended in empirical therapy of UTI in postmenopausal women. In many cases ultra-short and short protocols are preferable because of better compliance and tolerability. • Systemic menopausal hormonal therapy does not provide effective prophylaxis of cystitis in menopausal women. • Asymptomatic bacteriuria in postmenopausal women usually does not require any therapy. • Adherence inhibition to urothelial cells and protection against biofilm formation are the key mechanisms of the antiuroseptic treatment especially with respect to the risk of recurrent UTIs.